(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2025)
This work presents an unpublished Iberian inscription made on the base of an Attic skyphos which comes from the singular building of Mas Castellar (Pontós) destroyed in the last quarter of the 5th century BC, with the text taŕśabańar, which reproduces and completes the same text as one of the already published that comes from the same building: taŕśa[. The interpretation is clear, it is the name of the owner of the two skyphoi and probably of the house, taŕśabań. Both become the oldest Iberian inscriptions known based on stratigraphic chronology. The abundance of Greek graffiti is also noteworthy; they have been found grouped according to the text they bear, which suggests that they were made within the household itself rather than during the commercialization process, a fact that would further support the cultural hybridity of the building.